Retrieval-Oriented Design of Clinical Research Forms - Gall, W.; Eigenbauer, E.; Rasoul-Rockenschaub, S. (Methods of Information in Medicine, 2001)
Computerized clinical forms are subject to a wide variety of different requirements. They have to allow detailed documentation and must be user-friendly. State-of-the-art applications for design permit clinicians themselves to create their own forms as needed, with the various variables presented in different ways depending on their intended use. Often, however, only aspects of clinical documentation are considered, with no thought being given to subsequent data retrieval. This article presents guidelines for the retrieval-oriented design of clinical forms. It discusses where anticipatory measures for structuring forms are easier to accomplish than complex data linkage at the time of retrieval and analysis.
Keywords: Interface Design; Clinical Research Forms; Form Production; Retrievability